A parametric study of geosynthetic-reinforced column-supported embankments. Issue 3 (June 2014) - Yapage, N.N.S.; Liyanapathirana, D.S.
Abstract : ABSTRACT: This paper presents an extensive parametric study for geosynthetic-reinforced column-supported (GRCS) embankments. The analysis was carried out using the finite-element method based on the coupled-hydraulic modelling, incorporating the full geometry of the embankment and strain-softening behaviour of deep cement mixed (DCM) columns. The influencing factors considered in the parametric study were elastic modulus of DCM columns, area replacement ratio (ARR) based on spacing and diameter of DCM columns, elastic modulus and permeability of soft foundation soil, stiffness of the geosynthetic reinforcement, thickness of the platform layer and friction angle of the fill material. Embankment behaviour during the parametric study was investigated by comparing maximum total and differential settlements, maximum tension in the geosynthetic, maximum lateral deformation of columns, efficiency coefficient of columns and arching ratio. The influencing factors were ranked based on their degree of influence on the behaviour of the embankment. Results show that column spacing and diameter, which control the ARR, and elastic modulus of soft soil were the most important design parameters to be considered in GRCS design procedures. In comparison with an unreinforced column-supported embankment, by using a geosynthetic layer, lateral deformations can be reduced by about 10 times and differential settlements at the base of the embankment can be reduced by about three times. In addition, numerical results show that a thin platform layer was more efficient in transferring the embankment load to columns than a thick platform layer.